Approach to Abnormal Uterine Bleeding in Adolescents - Cenk Yaşa; Funda Güngör Uğurlucan (JCRPE, 2020)

(untitled)
This article reviews the current understanding and management of abnormal uterine bleeding (AUB) in adolescents. It is hoped that this review will provide readers with an approach to the evaluation and treatment of mild to severe uterine bleeding. AUB is a common problem which has significantly adverse effects on an affected adolescent’s quality of life. The most common underlying condition in AUB in adolescence is anovulation. During the evaluation, pregnancy, trauma and sexually transmitted diseases must be ruled out, regardless of history. It should be kept in mind that AUB during this period may be the first sign of underlying bleeding disorders. Although observation is sufficient in the mild form of AUB, at the other end of the spectrum life-threatening bleeding may necessitate the use of high doses of combined oral contraceptives, intravenous estrogen and/or interventional procedures.